2017
DOI: 10.1039/c7ra06709g
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption performance of methylimidazolium ionic liquids: towards novel ultra-wideband metamaterial absorbers

Abstract: The ultra-wideband absorption of microwaves was achieved by metamaterials based on methylimidazolium ionic liquids for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…The absorption at higher frequency presented the minimum RL for the sample with 2.5 phr of IL. The microwave absorption characteristic of these ER network loaded with IL may be attributed to the dielectric and conductive loss generated by the presence of free ions and anion–cation pairs, thus causing ionic conductivity and dielectric polarization . There is an optimum concentration of ions for the highest absorption of the radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption at higher frequency presented the minimum RL for the sample with 2.5 phr of IL. The microwave absorption characteristic of these ER network loaded with IL may be attributed to the dielectric and conductive loss generated by the presence of free ions and anion–cation pairs, thus causing ionic conductivity and dielectric polarization . There is an optimum concentration of ions for the highest absorption of the radiation.…”
Section: Resultsmentioning
confidence: 99%
“…However, they require some synthetic pathways which limits the scale‐up. Pure imidazolium‐based IL was recently reported to present strong microwave absorption in a broad microwave frequency range …”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66] Moreover, the ionic liquids have high dielectric-loss factors in the microwave range, which are desirable for fabricating microwave all-dielectric metamaterials. [67] The cavity injection method has been used to fabricate all-dielectric metamaterials based on ionic liquids. In one example, a 3D printer was employed to fabricate hollow annular groove unit cells.…”
Section: Cavity Injection Methodsmentioning
confidence: 99%
“…Therefore, it was conceivable that the interaction mechanism between GO and MWs would become more complicated when GO was functionalized with ILs. Because ILs could become strong absorbers of MWs because of their special polarization structure containing anion–cation pairs. Recent literature surveys ,, clearly revealed that it was a relatively unexplored area of research referring to both the synthesis mechanism of the IL-GO hybrid and the microscale interaction between the IL-GO hybrid and polymer matrix under the function of MWs. Therefore, for the polymer-containing IL-GO hybrid, it was necessary to study its curing mechanism and overall performance under the action of MWs.…”
Section: Introductionmentioning
confidence: 99%